Tipton, R. (2024). The Routledge Guide to Teaching Ethics in Translation and Interpreting Education. London: Routledge. https://doi.org/10.4324/9781003098485 (pp. 236) - Yin, Heng; Lyu, Qi (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
/